Fronteira e territorialização: uma cartografia da Revolução Federalista (1891-1896) a partir das redes de relações de poder da família Silva Tavares na região platina - Andrade, Gustavo Figueira (2021)
This doctorate thesis has as its theme “Border and territorialization: a cartography of the Federalist Revolution (1891-1896) from the networks of power relations of General João Nunes da Silva Tavares and his family in La Plata region. The research developed is linked to the Research Line “Frontier, Politics and Society” and had the support of the CAPES/FAPERGS scholarship and the CAPES Interuniversity Exchange Doctorate Scholarship from August 1, 2019 to February 2, 2020. The thesis focused on the analysis of the development of the Federalist Revolution, based on the participation of the Silva Tavares family and the constitution of their networks of social relations. For this purpose, it proposes a new chronology of the conflict and a cartography of the Federalist Revolution based on the territorialization of power expressed by the networks of personal relationships (family, political and military relations) of the Silva Tavares family, especially based on letters and telegrams exchanged by federalist chiefs in a territory that extended not only over Rio Grande do Sul, but also to other Brazilian states, as well as to several Departments of the Oriental Republic of Uruguay and Coastal Provinces of the Argentinian Republic within the period of the conflict, indicating the existence of a network of relationships in La Plata territory. Our perspective goes beyond the narratives built from official sources and broadens the understanding about this conflict. Based on unprecedent sources produced by federalists, which highlight the participation of Silva Tavares in this conflict, we propose a new chronology for thinking about the Federalist Revolution, and in this sense, we demonstrate that it began in 1891 and lasted until 1896, a period marked by intense participation of this family. To reveal the coverage of this family's networks, we developed a cartography that shows the national and international scope of the conflict and the family relationships, as well as its leading role in the political field and not just the military conduct of the conflict. Yet starting from the cartography of the Revolution, we defend the existence of a revolutionary region shaped by war during the 19th century; we present some of its common characteristics that brought individuals together and created a regional identity. The permanence of traditional practices expresses a logic of thinking about politics and war, practices used to articulate and mobilize men and resources during the conflict, constituting, together with the experience and coexistence in combat, explanatory keys to understand the characteristics of the Revolution. The analysis of rural and urban social networks formed around the Silva Tavares family during the conflict allows us to identify the existence of a group closer to this family; we demonstrate the permanence of traditional practices which express a logic of thinking about politics and war, practices used to articulate and mobilize men and resources during the conflict, constituting, together with the experience and coexistence in combat, explanatory keys to understanding the characteristics of the Revolution. These aspects are in line with our thesis, stating that this conflict was organized within some important and powerful families and that they articulated and mobilized other dissatisfied leaders around a project of broad power that also contemplated their interests, forming a strong link immersed in a power structure, providing this family with a territory of power under its influence.